2019
DOI: 10.1097/corr.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Did Osteoblastic Cell Therapy Improve the Prognosis of Pre-fracture Osteonecrosis of the Femoral Head? A Randomized, Controlled Trial

Abstract: Background In patients with nontraumatic osteonecrosis of the femoral head (ONFH), implantation of bone marrow aspirate concentrate (BMAC) could delay the progression of osteonecrosis and improve symptoms in pre-fracture ONFH. However, the BMAC content, especially in osteoblastic stem cells, could have an important individual variability. An autologous osteoblastic cell product could improve the effect of such cell-based therapy. Questions/purposes (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…This meta-analysis showed that therapy with stem cells for early-stage ONFH could significantly have better outcomes on preventing collapse of femoral head and delaying the time for THR in the long term contributing to a better survival. Safety analysis also showed that there were fewer adverse events such as pain, fever, and nausea by adopting this therapy [20,[22][23][24], which was also supported by several other studies [13,41,42]. Besides, compared with control groups, we found that a significant difference was existed on the collapse of femoral head during follow-up of more than 60 months and THR head more than 36 months.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This meta-analysis showed that therapy with stem cells for early-stage ONFH could significantly have better outcomes on preventing collapse of femoral head and delaying the time for THR in the long term contributing to a better survival. Safety analysis also showed that there were fewer adverse events such as pain, fever, and nausea by adopting this therapy [20,[22][23][24], which was also supported by several other studies [13,41,42]. Besides, compared with control groups, we found that a significant difference was existed on the collapse of femoral head during follow-up of more than 60 months and THR head more than 36 months.…”
Section: Discussionsupporting
confidence: 81%
“…2) and no statistical difference between groups at 10 6 or 10 7 magnitude. Sensitivity analysis to investigate high heterogeneity in the subgroup with 10 6 cell number revealed that there was a statistical difference after excluding study by Hauzeur et al [22] using a random effects model (I 2 , 0%; RR, 0.31; 95% CI, 0.22 to 0.43; P < .00001).…”
Section: Total Hip Replacementmentioning
confidence: 94%
See 3 more Smart Citations